Fabricación y caracterización de dispositivos termoeléctricos a base de nanotubos de Carbono (2017)
The objective of this project is the fabrication of thermoelectric devices based on carbon nanotubes (CNT) and polianiline (PANI) and the measurement of the figure of merit, ZT, for these devices using the transient Harman method. A methodology was developed to produce CNT thin films on silicon substrates in an homogeneous and consistent manner in order to produce these devices. Values of up to 1,46 « 0,41 were found which corresponds to an efficiency of approximately 15 %. It was found that the addition of PANI reduces slightly the thermoelectric properties compared to devices made only of CNT.